2019
DOI: 10.3390/antiox8110519
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C in Plants: From Functions to Biofortification

Abstract: Vitamin C (l-ascorbic acid) is an excellent free radical scavenger, not only for its capability to donate reducing equivalents but also for the relative stability of the derived monodehydroascorbate radical. However, vitamin C is not only an antioxidant, since it is also a cofactor for numerous enzymes involved in plant and human metabolism. In humans, vitamin C takes part in various physiological processes, such as iron absorption, collagen synthesis, immune stimulation, and epigenetic regulation. Due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(172 citation statements)
references
References 234 publications
6
160
1
5
Order By: Relevance
“…The research carried out represents a valuable source of data which allowed to eliminate the gap between laboratory data on single plant extracts (presented in papers by Godlewska et al [ 41 ] and Godlewska et al [ 42 ]) and field tests combined with fertilisers. This study provides a crucial knowledge about the effects of botanical extracts on crops under real-field conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research carried out represents a valuable source of data which allowed to eliminate the gap between laboratory data on single plant extracts (presented in papers by Godlewska et al [ 41 ] and Godlewska et al [ 42 ]) and field tests combined with fertilisers. This study provides a crucial knowledge about the effects of botanical extracts on crops under real-field conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Other factors that may affect its content in plants include genotype, weather, cultivation and harvesting methods, maturity as well as postharvest treatments. The high light intensity and less frequent irrigation positively affect the content of vitamin C [ 38 , 41 ]. The conducted research showed that the application of botanical extracts increased the content of vitamin C in celeriac leaves – mostly after the second application (e.g., Vo R UAE and Hp H MH).…”
Section: Discussionmentioning
confidence: 99%
“…24). Hence, vitamin C is a good free radical scavenger in vitro and in vivo by both its ability to act as an electron donor with a redox potential and the relative stability and unreactivity of MDHA (Paciolla et al 2019). By its capacity to donate reducing equivalents, vitamin C also contributes to several biochemical reactions.…”
Section: Perspectivesmentioning
confidence: 99%
“…Plant-derived ascorbate is the major source of vitamin C in the human diet. Indeed, L-ascorbate is abundant in plants, but with contents significantly different among plant species and cultivars (Paciolla et al 2019;Smirnoff 2018). Ascorbate concentrations vary between the organs, with highest contents in the aerial parts such as leaves and flowers and lower contents in less photosynthetically organs such as roots and stems.…”
Section: Perspectivesmentioning
confidence: 99%
“…AsA is a cofactor in different enzymatic reactions and participates in a variety of biological functions, both in mammals and plants [1]. In the human diet, AsA has gained popularity as antioxidant especially for its ability to counteract the over-production of free radicals in cells, and as a natural chemopreventive for the reduction of risk factors for cardiovascular diseases and cancer [2][3][4].…”
Section: Introductionmentioning
confidence: 99%